2015 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2015
DOI: 10.1109/iros.2015.7354014
|View full text |Cite
|
Sign up to set email alerts
|

Developing an embodied gait on a compliant quadrupedal robot

Abstract: Abstract-Incorporating the body dynamics of compliant robots into their controller architectures can drastically reduce the complexity of locomotion control. An extreme version of this embodied control principle was demonstrated in highly compliant tensegrity robots, for which stable gait generation was achieved by using only optimized linear feedback from the robot's sensors to its actuators. The morphology of quadrupedal robots has previously been used for sensing and for control of a compliant spine, but ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…This output could then be used as a command sequence sent to actuators. However, this approach was further complicated in a quadrupedal robot [19]. Nakajima et al [57] have used a model of a soft robotic arm inspired by the octopus.…”
Section: Physical Reservoir Computingmentioning
confidence: 99%
See 1 more Smart Citation
“…This output could then be used as a command sequence sent to actuators. However, this approach was further complicated in a quadrupedal robot [19]. Nakajima et al [57] have used a model of a soft robotic arm inspired by the octopus.…”
Section: Physical Reservoir Computingmentioning
confidence: 99%
“…This very much blurs the boundaries between the brain as the seat of computing and the "mere physical body," in accordance with biological reality, which will be discussed in the next section. However, thus far the examples of this type [28,57,58,11,19,37] have a theoretical or proof-of-concept character, and their applicability remains to be proven ( Figure 9I-J).…”
Section: Morphological Computationmentioning
confidence: 99%
“…By combining the body feedback with some additional computational power (e.g. a 'brain'), more complex locomotion tasks can be accomplished (Degrave et al, 2015). The computations that naturally occur in the body are then augmented with a small 'brain' to achieve partially embodied control.…”
Section: Introductionmentioning
confidence: 99%
“…The computations that naturally occur in the body are then augmented with a small 'brain' to achieve partially embodied control. In Degrave et al (2015) this was found to be necessary for gait generation with a quadruped robot. In Burms et al (2015) and Urbain et al (2017), more complex tasks were addressed using, respectively, a tensegrity robot and a mass-spring network.…”
Section: Introductionmentioning
confidence: 99%
“…They show a walking pattern that looks natural and energy efficient compared to traditional stiff controlled robots. In other fields of robotics, we can also cite the works of Iida and Pfeifer (2006) or Degrave et al (2015), in which dynamical properties of compliant quadruped robots are used to provide low power consumption, to reduce controller computational complexity, and to observe natural transitions between gaits. Examples that clearly benefit from compliance to improve moving can also be found, among others, in Cham et al (2004) which focuses on hexapod locomotion.…”
Section: Introductionmentioning
confidence: 99%